Handling Community Cases of Self-injury (Barcode) in Early Adolescents Using Self-Talk Therapy - Luluk Setyowati; Fadjarijah Nurulita; Andreas Adi Haryanto (CV Projurnal Mitra Publikasi, 2025)
Self-injury is a non-suicidal self-harm disorder that seems to be largely maintained by negative reinforcement, for example that the behavior is reported to rapidly reduce negative emotions and unpleasant emotional arousal. The self-injury behavior is carried out with the aim of overcoming it with trauma-related symptoms such as anger and/or disgust directed at oneself, so that the individual feels positive feelings or feels better. The method used to handle these problems is to use self-talk therapy, which is a form of intrapersonal communication, meaning that communication is carried out by the individual to himself, either consciously or unconsciously. The subjects in this study consisted of students aged 12-15 years, consisting of 13-15 children. The implementation stage of self-talk therapy consists of four sessions, session I consists of pre-test, psychoeducation and the initial understanding stage. Session II is an in-depth session on self-talk, students are divided into two groups with lighter and heavier problems. Sessions III and IV are sessions on understanding how to do negative to positive self-talk and evaluation. As a result of this activity, the student's self-injury behavior or barcode is reduced or never done again. It can be concluded that the average teenager is self-injury because he does not understand the impact, with self-talk therapy students are more able to control themselves and begin to be able to distinguish negative thoughts and understand how to direct positive thoughts.